Endovascular Treatment of Intracranial Dural Arteriovenous Fistulas. (1st February 2014) - VanLandingham, Matthew; Fox, Benjamin; Hoit, Daniel; Elijovich, Lucas; Arthur, Adam S.
Abstract: Endovascular treatment options for dural arteriovenous fistulas (DAVFs) have vastly expanded and become progressively safer in the last several years. Angiographic imaging systems have improved, catheter technology has advanced, and liquid embolic and coil options have increased. As a likely result, an increasing proportion of DAVFs are treated via an endovascular approach. In addition to allowing physicians to appreciate and treat lesions better, varied approaches have been developed. The "plug and push" technique and the new availability of dimethyl sulfoxide--compatible dual lumen balloons have allowed safer and more thorough transarterial treatments. Transvenous treatment has proved to be a valuable technique for some lesions. Hybrid approaches with surgical assisted access to vascular structures have been successfully used to treat more challenging fistulas.